A high-stability lithium battery pole piece and its preparation method and application

By using the synergistic effect of the first and second binders in lithium-ion batteries, the active materials are modified and the high-stability lithium battery electrodes are formed, which solves the problem of insufficient rate performance and energy density of lithium-ion batteries, and significantly improves the cycle stability and service life of the battery.

CN119517990BActive Publication Date: 2025-04-11NANTONG JIANGHAI NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510089272.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The rate performance and energy density of existing lithium-ion batteries are insufficient, and the volume expansion of silicon-carbon negative electrodes leads to a decrease in battery life.

Method used

Using the synergistic action of the first and second binders, the modified active material is spray-drying and fibrosis to form a high-stability lithium battery electrode sheet, inhibiting the volume expansion of active particles, and improving the rate performance and cycle stability of the battery.

Benefits of technology

When the total content of binder is low, the volume expansion of thick electrode active particles is effectively suppressed, the rate performance and cycle stability of the battery are improved, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517990B_ABST
    Figure CN119517990B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium-ion batteries, and specifically discloses a high-stability lithium battery pole piece and its preparation method and application; the preparation method comprises the following steps: S1: adding a first binder to deionized water and dispersing it evenly, adding an oxidized conductive filler and stirring and mixing, obtaining a first layer of a binder solution, adding an active material and stirring and mixing, spray drying at 150-160°C, obtaining a modified active material; S2: dry-mixing the modified active material, the second binder, and the conductive filler for 5-10 hours; subjecting it to a fiberization treatment at 150-200°C for 5-10 hours to obtain a composite active material; S3: rolling the composite active material onto the surface of a current collector to form an active layer of 50-300 μm; obtaining a high-stability lithium battery pole piece. The first binder comprises one or more of polyacrylic acid, sodium carboxymethyl cellulose, and polyethylene glycol; the second binder is polytetrafluoroethylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and specifically discloses a high-stability lithium battery pole piece and a preparation method and application thereof. Background Art

[0002] At present, the large-scale industrialization of pure electric vehicles still faces problems such as charging anxiety, mileage anxiety, and high costs. Among them, how to significantly improve the rate performance and energy density of lithium-ion batteries has attracted the most attention. As the main component of the battery, the electrode has a great influence on the performance of the energy storage device. The use of silicon-carbon negative electrodes can improve the battery energy density, but it has problems such as volume expansion, causing the electrode to crack and the battery life to drop sharply.

[0003] Binders with linear macromolecular structures rich in functional groups, such as sodium carboxymethyl cellulose and polyacrylic acid, have a good effect in inhibiting volume expansion and can be used to graft linear conductive molecules, but their toughness needs to be improved; polytetrafluoroethylene with a dry structure can provide a good three-dimensional bonding effect after fiberization, but the amount of polytetrafluoroethylene added to the pure dry electrode is large, which will affect the energy density; in summary, it is of great significance to study a high-stability lithium battery electrode and its preparation method that has a low total binder content, can inhibit the volume expansion of thick electrode active particles, and can improve battery rate performance and cycle stability. Summary of the invention

[0004] The purpose of the present invention is to provide a high-stability lithium battery pole piece and a preparation method and application thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a high-stability lithium battery pole piece comprises the following steps:

[0007] S1: adding the first binder to deionized water and dispersing the mixture uniformly, adding the oxidized conductive filler and stirring to obtain a first binder layer solution, adding the active material and stirring to obtain a first binder layer solution, and spray drying the mixture at 150-160° C. to obtain a modified active material;

[0008] S2: dry-mixing the modified active material, the second binder, and the conductive filler for 5 to 10 hours; and fiberizing the mixture at 150 to 200° C. for 5 to 10 hours to obtain a composite active material;

[0009] S3: Roll the composite active material onto the surface of the current collector to form an active layer of 50-300 μm; and obtain a high-stability lithium battery electrode.

[0010] More optimally, the first bonding layer solution includes the following raw materials: 0.01~1.5wt% oxidized conductive filler, 0.5~1.5wt% first binder, and the rest is deionized water; in the raw materials of the modified active material, the ratio of active material to first binder is 99~99.5:(0.5~1).

[0011] More optimally, in the raw materials of the composite active material, the mass ratio of the modified active material, the second binder, and the conductive filler is (95~96): (1.5~2): (2~3).

[0012] More optimally, the preparation of the oxidized conductive filler includes the following steps: oxidizing the conductive filler with 10-20wt% hydrogen peroxide for 1-10h, filtering, washing, and drying to obtain the oxidized conductive filler; the conductive filler includes one or more of carbon nanotubes, carbon fibers, graphene, and conductive carbon black.

[0013] More optimally, the preparation of the oxidized conductive filler includes the following steps: immersing the conductive filler in 20% hydrogen peroxide for oxidation treatment for 6 hours, taking it out and drying it to obtain the oxidized conductive filler; the conductive filler is conductive carbon black.

[0014] More optimally, the active material is a silicon-carbon negative electrode active material; the preparation process is: take nickel powder and silicon powder, ball mill under argon atmosphere to obtain a mixed powder; take the mixed powder and melamine, ball mill under argon atmosphere, heat to 650~700℃ in argon atmosphere and keep warm for 3~4h to obtain a silicon-carbon negative electrode active material.

[0015] More optimally, the preparation process of the active material is as follows: take 0.5 parts of nano nickel powder (average particle size of 100nm) and 1 part of micron silicon powder (average particle size of 3μm), ball mill for 2h under argon atmosphere, the ball milling speed is 500r / min, and the diameter of the grinding ball is 15mm; to obtain a mixed powder; take 1.5 parts of the mixed powder and 1 part of melamine, ball mill for 4h under argon atmosphere, put them in a tubular furnace, heat to 650°C in argon atmosphere, keep warm for 4h, to obtain a silicon-carbon negative electrode active material; the ball milling speed is 400r / min, and the diameter of the grinding ball is 6mm.

[0016] More optimally, the first binder includes one or more of polyacrylic acid, sodium carboxymethyl cellulose, and polyethylene glycol; and the second binder is polytetrafluoroethylene.

[0017] Preferably, the first binder comprises polyacrylic acid and multi-arm polyethylene glycol in a mass ratio of (7-8):(2-3).

[0018] More optimally, the preparation of the multi-arm polyethylene glycol comprises the following steps: Step 1: Take octahydroxybutylated cage-shaped silsesquioxane and 3,3,3-trifluoropropionyl chloride, add dimethyl sulfoxide and stir evenly, stir evenly at 25-35° C. and continue to react for 10-12 hours, remove the solvent, and obtain modified POSS;

[0019] Step 2: Take modified POSS and four-arm epoxy polyethylene glycol, add dimethyl sulfoxide and stir evenly, heat to 120-150° C., continue to react for 6-8 hours after stirring evenly, remove the solvent, and obtain multi-arm polyethylene glycol.

[0020] More optimally, the modified POSS comprises the following raw materials, calculated by mass: 15-20 parts of octahydroxybutylated cage-shaped silsesquioxane, 10-15 parts of 3,3,3-trifluoropropionyl chloride; the multi-arm polyethylene glycol comprises the following raw materials, calculated by mass: 25-30 parts of modified POSS, 20-25 parts of four-arm epoxy polyethylene glycol.

[0021] Compared with the prior art, the beneficial effects achieved by the present invention are: through the synergistic effect of the first binder and the second binder, the production of thick electrodes is achieved with a low total binder content, the binder failure problem caused by the volume expansion of active particles in the thick electrode is suppressed, and the rate performance and cycle stability of the battery are improved;

[0022] The first binder includes polyacrylic acid and multi-arm polyethylene glycol in a mass ratio of (7~8): (2~3). Compared with a single binder, the combination of multiple binders is beneficial to improving rheological properties. Polyacrylic acid has a good effect of inhibiting volume expansion, but its toughness is insufficient. The prepared electrode is prone to cracking, which affects the battery performance. Therefore, an appropriate amount of multi-arm polyethylene glycol is introduced. Polyethylene glycol itself has good compatibility with polyacrylic acid and can give the binder high ionic conductivity. The multi-arm polyethylene glycol prepared by the present invention is first based on octahydroxybutylated cage-shaped silsesquioxane and grafted with 3,3,3-trifluoropropionyl chloride to obtain modified POSS, wherein the octahydroxybutylated cage-shaped silsesquioxane helps to improve the thermal stability and mechanical properties of the binder and give it good flexibility. 3,3,3-trifluoropropionyl chloride contains fluorine and has a similar structure to the second binder, which can enhance the affinity between the two binders. In the next step, the modified POSS is grafted with four-arm epoxy polysiloxane. The multi-arm polyethylene glycol of ethylene glycol can improve the crosslinking degree of the first binder in the subsequent steps, form an appropriate network structure, improve cohesion, alleviate the problems of cracking and falling off during use, and improve battery performance; the addition amount of each component of the above-mentioned multi-arm polyethylene glycol needs to be controlled, excessive addition of 3,3,3-trifluoropropionyl chloride will result in octahydroxybutylated cage-shaped silsesquioxane having no hydroxyl group that can participate in the subsequent reaction, and excessive addition of modified POSS will result in all epoxy groups of the multi-arm polyethylene glycol participating in the reaction, and it will not play the role of a crosslinking agent in the subsequent steps, and the addition amount of the multi-arm polyethylene glycol also needs to be controlled. Excessive addition will lead to the problem of excessive crosslinking, which will lead to increased brittleness and reduced battery energy density and service life; in summary, the present invention uses a composite binder and utilizes its synergistic effect to prepare a high-stability lithium battery electrode sheet with a small amount of binder added, which can inhibit the volume expansion of thick electrode active particles and improve battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the surface state of the electrode of Example 1 after 200 cycles;

[0024] Figure 2 This is the surface state of the electrode of comparative example 1 after 200 cycles. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Unless otherwise specified, the following parts are by mass and mass ratio;

[0027] Example 1: S1: Add the first binder to deionized water and disperse it evenly, add the oxidized conductive filler and stir and mix to obtain a first binder layer solution, add the active material and stir and mix, and spray dry at 160° C. to obtain a modified active material;

[0028] S2: dry-mixing the modified active material, the second binder and the conductive filler in a mass ratio of 96:2:2 for 6 hours; and subjecting the mixture to a fiberization treatment at 180° C. for 8 hours to obtain a composite active material;

[0029] S3: rolling the composite active material onto the surface of the current collector to form an active layer of 100 μm; obtaining a high-stability lithium battery pole piece;

[0030] The first bonding layer solution includes the following raw materials: 1.0wt% oxidized conductive filler, 1.5wt% first bonding agent, and the rest is deionized water; in the raw materials of the modified active material, the mass ratio of the active material to the first bonding agent is 99:1; the first bonding agent is polyacrylic acid.

[0031] Example 2: S1: Add the first binder to deionized water and disperse it evenly, add the oxidized conductive filler and stir to obtain a first binder layer solution, add the active material and stir to obtain a first binder layer solution, spray dry at 160°C to obtain a modified active material;

[0032] S2: dry-mixing the modified active material, the second binder and the conductive filler in a mass ratio of 96:2:2 for 6 hours; and subjecting the mixture to a fiberization treatment at 180° C. for 8 hours to obtain a composite active material;

[0033] S3: rolling the composite active material onto the surface of the current collector to form an active layer of 100 μm; obtaining a high-stability lithium battery pole piece;

[0034] The first bonding layer solution includes the following raw materials: 1.0wt% oxidized conductive filler, 1.5wt% first bonding agent, and the rest is deionized water; in the raw materials of the modified active material, the mass ratio of the active material to the first bonding agent is 99:1; the first bonding agent is polyacrylic acid and multi-arm polyethylene glycol in a mass ratio of 7:3;

[0035] The preparation of the multi-arm polyethylene glycol comprises the following steps: taking 17 parts of octahydroxybutylated cage-shaped silsesquioxane and 10 parts of 3,3,3-trifluoropropionyl chloride, adding 200 parts of dimethyl sulfoxide and stirring evenly, stirring evenly at 30° C. and continuing the reaction for 12 hours, removing the solvent, and obtaining modified POSS;

[0036] Take 25 parts of modified POSS and 20 parts of four-arm epoxy polyethylene glycol, add 200 parts of dimethyl sulfoxide and stir evenly, heat to 150° C., continue to react for 8 hours after stirring evenly, remove the solvent, and obtain multi-arm polyethylene glycol.

[0037] Example 3: S1: adding the first binder to deionized water and dispersing it evenly, adding the oxidized conductive filler and stirring and mixing to obtain a first binder layer solution, adding the active material and stirring and mixing, and spray drying at 160° C. to obtain a modified active material;

[0038] S2: dry-mixing the modified active material, the second binder and the conductive filler in a mass ratio of 96:2:2 for 6 hours; and subjecting the mixture to a fiberization treatment at 180° C. for 8 hours to obtain a composite active material;

[0039] S3: rolling the composite active material onto the surface of the current collector to form an active layer of 100 μm; obtaining a high-stability lithium battery pole piece;

[0040] The first bonding layer solution includes the following raw materials: 1.0wt% oxidized conductive filler, 1.5wt% first bonding agent, and the rest is deionized water; in the raw materials of the modified active material, the mass ratio of the active material to the first bonding agent is 99:1; the first bonding agent is polyacrylic acid and multi-arm polyethylene glycol in a mass ratio of 7:3;

[0041] The preparation of the multi-arm polyethylene glycol comprises the following steps: taking 15 parts of octahydroxybutylated cage-shaped silsesquioxane and 10 parts of 3,3,3-trifluoropropionyl chloride, adding 200 parts of dimethyl sulfoxide and stirring evenly, stirring evenly at 30° C. and continuing the reaction for 12 hours, removing the solvent, and obtaining modified POSS;

[0042] Take 25 parts of modified POSS and 20 parts of four-arm epoxy polyethylene glycol, add 200 parts of dimethyl sulfoxide and stir evenly, heat to 150° C., continue to react for 8 hours after stirring evenly, remove the solvent, and obtain multi-arm polyethylene glycol.

[0043] Example 4: S1: adding the first binder to deionized water and dispersing it evenly, adding the oxidized conductive filler and stirring and mixing to obtain a first binder layer solution, adding the active material and stirring and mixing, and spray drying at 160° C. to obtain a modified active material;

[0044] S2: dry-mixing the modified active material, the second binder and the conductive filler in a mass ratio of 96:2:2 for 6 hours; and subjecting the mixture to a fiberization treatment at 180° C. for 8 hours to obtain a composite active material;

[0045] S3: rolling the composite active material onto the surface of the current collector to form an active layer of 100 μm; obtaining a high-stability lithium battery pole piece;

[0046] The first bonding layer solution includes the following raw materials: 1.0wt% oxidized conductive filler, 1.5wt% first bonding agent, and the rest is deionized water; in the raw materials of the modified active material, the mass ratio of the active material to the first bonding agent is 99:1; the first bonding agent is polyacrylic acid and multi-arm polyethylene glycol in a mass ratio of 7:3;

[0047] The preparation of the multi-arm polyethylene glycol comprises the following steps: taking 20 parts of octahydroxybutylated cage-shaped silsesquioxane and 15 parts of 3,3,3-trifluoropropionyl chloride, adding 200 parts of dimethyl sulfoxide and stirring evenly, stirring evenly at 30° C. and continuing the reaction for 12 hours, removing the solvent, and obtaining modified POSS;

[0048] Take 30 parts of modified POSS and 25 parts of four-arm epoxy polyethylene glycol, add 200 parts of dimethyl sulfoxide and stir evenly, heat to 150° C., continue to react for 8 hours after stirring evenly, remove the solvent, and obtain multi-arm polyethylene glycol.

[0049] Comparative Example 1 (polytetrafluoroethylene is not added, and the remaining steps are the same as those of Example 1): S1: adding the first binder to deionized water and dispersing it evenly, adding the oxidized conductive filler and stirring and mixing to obtain a first binder layer solution, adding the active material and stirring and mixing, and spray drying at 160° C. to obtain a modified active material;

[0050] S2: dry-mixing the modified active material and the conductive filler at a mass ratio of 98:2 for 6 hours; treating the mixture at 180° C. for 8 hours to obtain a composite active material;

[0051] S3: rolling the composite active material onto the surface of the current collector to form an active layer of 100 μm; obtaining a high-stability lithium battery pole piece;

[0052] The first bonding layer solution includes the following raw materials: 1.0wt% oxidized conductive filler, 1.5wt% first bonding agent, and the rest is deionized water; in the raw materials of the modified active material, the mass ratio of the active material to the first bonding agent is 99:1; the first bonding agent is polyacrylic acid.

[0053] Comparative Example 2 (changing the ratio of the first binder raw material, the other method steps are consistent with Example 2): S1: adding the first binder to deionized water and dispersing it evenly, adding the oxidized conductive filler and stirring and mixing to obtain a first binder layer solution, adding the active material and stirring and mixing, and spray drying at 160° C. to obtain a modified active material;

[0054] S2: dry-mixing the modified active material, the second binder and the conductive filler in a mass ratio of 96:2:2 for 6 hours; and subjecting the mixture to a fiberization treatment at 180° C. for 8 hours to obtain a composite active material;

[0055] S3: rolling the composite active material onto the surface of the current collector to form an active layer of 100 μm; obtaining a high-stability lithium battery pole piece;

[0056] The first bonding layer solution includes the following raw materials: 1.0wt% oxidized conductive filler, 1.5wt% first bonding agent, and the rest is deionized water; in the raw materials of the modified active material, the mass ratio of the active material to the first bonding agent is 99:1; the first bonding agent is polyacrylic acid and multi-arm polyethylene glycol in a mass ratio of 7:4;

[0057] The preparation of the multi-arm polyethylene glycol comprises the following steps: taking 17 parts of octahydroxybutylated cage-shaped silsesquioxane and 10 parts of 3,3,3-trifluoropropionyl chloride, adding 200 parts of dimethyl sulfoxide and stirring evenly, stirring evenly at 30° C. and continuing the reaction for 12 hours, removing the solvent, and obtaining modified POSS;

[0058] Take 25 parts of modified POSS and 20 parts of four-arm epoxy polyethylene glycol, add 200 parts of dimethyl sulfoxide and stir evenly, heat to 150° C., continue to react for 8 hours after stirring evenly, remove the solvent, and obtain multi-arm polyethylene glycol.

[0059] Comparative Example 3 (changing the raw material ratio of modified POSS, the other method steps are consistent with Example 2): S1: adding the first binder to deionized water and dispersing it evenly, adding the oxidized conductive filler and stirring and mixing to obtain a first binder layer solution, adding the active material and stirring and mixing, and spray drying at 160° C. to obtain a modified active material;

[0060] S2: dry-mixing the modified active material, the second binder and the conductive filler in a mass ratio of 96:2:2 for 6 hours; and subjecting the mixture to a fiberization treatment at 180° C. for 8 hours to obtain a composite active material;

[0061] S3: rolling the composite active material onto the surface of the current collector to form an active layer of 100 μm; obtaining a high-stability lithium battery pole piece;

[0062] The first bonding layer solution includes the following raw materials: 1.0wt% oxidized conductive filler, 1.5wt% first bonding agent, and the rest is deionized water; in the raw materials of the modified active material, the mass ratio of the active material to the first bonding agent is 99:1; the first bonding agent is polyacrylic acid and multi-arm polyethylene glycol in a mass ratio of 7:3;

[0063] The preparation of the multi-arm polyethylene glycol comprises the following steps: taking 17 parts of octahydroxybutylated cage-shaped silsesquioxane and 6 parts of 3,3,3-trifluoropropionyl chloride, adding 200 parts of dimethyl sulfoxide and stirring evenly, stirring evenly at 30° C. and continuing the reaction for 12 hours, removing the solvent, and obtaining modified POSS;

[0064] Take 25 parts of modified POSS and 20 parts of four-arm epoxy polyethylene glycol, add 200 parts of dimethyl sulfoxide and stir evenly, heat to 150° C., continue to react for 8 hours after stirring evenly, remove the solvent, and obtain multi-arm polyethylene glycol.

[0065] Comparative Example 4 (changing the raw material ratio of multi-arm polyethylene glycol, the other method steps are consistent with Example 2): S1: adding the first binder to deionized water and dispersing it evenly, adding the oxidized conductive filler and stirring and mixing to obtain a first binder layer solution, adding the active material and stirring and mixing, and spray drying at 160° C. to obtain a modified active material;

[0066] S2: dry-mixing the modified active material, the second binder and the conductive filler in a mass ratio of 96:2:2 for 6 hours; and subjecting the mixture to a fiberization treatment at 180° C. for 8 hours to obtain a composite active material;

[0067] S3: rolling the composite active material onto the surface of the current collector to form an active layer of 100 μm; obtaining a high-stability lithium battery pole piece;

[0068] The first bonding layer solution includes the following raw materials: 1.0wt% oxidized conductive filler, 1.5wt% first bonding agent, and the rest is deionized water; in the raw materials of the modified active material, the mass ratio of the active material to the first bonding agent is 99:1; the first bonding agent is polyacrylic acid and multi-arm polyethylene glycol in a mass ratio of 7:3;

[0069] The preparation of the multi-arm polyethylene glycol comprises the following steps: taking 17 parts of octahydroxybutylated cage-shaped silsesquioxane and 10 parts of 3,3,3-trifluoropropionyl chloride, adding 200 parts of dimethyl sulfoxide and stirring evenly, stirring evenly at 30° C. and continuing the reaction for 12 hours, removing the solvent, and obtaining modified POSS;

[0070] Take 25 parts of modified POSS and 15 parts of four-arm epoxy polyethylene glycol, add 200 parts of dimethyl sulfoxide and stir evenly, heat to 150° C., continue to react for 8 hours after stirring evenly, remove the solvent, and obtain multi-arm polyethylene glycol.

[0071] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: conductive carbon black (Article No. 220623135935, Cabot Conductive Carbon Black 72, Kramar); polyacrylic acid (Article No. JR1196, Hubei Junrui Biotechnology); melamine (CAS: 108-78-1); polytetrafluoroethylene (Article No. S24392, Shanghai Yuanye); four-arm epoxy polyethylene glycol (molecular weight 2k, Shaanxi Xinyan Bomei Biotechnology); octahydroxybutylated cage-shaped silsesquioxane (99%, Qiyue Biological, Article No.: 3131); dimethyl sulfoxide (CAS: 67-68-5); 3,3,3-trifluoropropionyl chloride (CAS: 41463-83-6).

[0072] Experiment: Take the high-stability lithium battery pole pieces prepared in Examples 1 to 3 and Comparative Examples 1 to 4, assemble the batteries according to the conventional battery assembly process and test them. The specific data are shown in the table below;

[0073]

[0074] Conclusion: In comparative example 1, polytetrafluoroethylene is not added, and the remaining method steps are consistent with embodiment 1, and the performance is significantly reduced; comparative examples 2 to 4 are set based on embodiment 2, and comparative example 2 changes the ratio of binder raw materials, and the amount of auxiliary cross-linking agent added is increased. Excessive cross-linking leads to performance degradation, which shows the importance of controlling the dosage; comparative example 3 changes the raw material ratio of modified POSS and reduces the amount of 3,3,3-trifluoropropionyl chloride added, and the performance is not as good as the embodiment; the raw material ratio of multi-arm polyethylene glycol is changed, and the amount of four-arm epoxy polyethylene glycol added is reduced, resulting in a decrease in cross-linking degree and a significant decrease in performance; in summary, the high-stability lithium battery pole piece prepared by the present invention has good energy density and good cycle performance.

[0075] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a high-stability lithium battery pole piece, characterized in that: The following steps are involved: S1: adding the first binder to deionized water and dispersing the mixture uniformly, adding the oxidized conductive filler and stirring to obtain a first binder layer solution, adding the active material and stirring to obtain a first binder layer solution, and spray drying the mixture at 150-160° C. to obtain a modified active material; S2: dry-mixing the modified active material, the second binder, and the conductive filler for 5 to 10 hours; and fiberizing the mixture at 150 to 200° C. for 5 to 10 hours to obtain a composite active material; S3: rolling the composite active material onto the surface of the current collector to form an active layer of 50-300 μm; A high-stability lithium battery electrode is obtained; The first binder is polyacrylic acid and multi-arm polyethylene glycol in a mass ratio of (7-8): (2-3); The preparation method of the multi-arm polyethylene glycol is as follows: octahydroxybutylated cage-shaped silsesquioxane and 3,3,3-trifluoropropionyl chloride are added with dimethyl sulfoxide and stirred evenly, and the mixture is stirred evenly at 25-35° C. and then reacted for 10-12 hours, and the solvent is removed to obtain modified POSS; Take modified POSS and four-arm epoxy polyethylene glycol, add dimethyl sulfoxide and stir evenly, heat to 120-150°C, stir evenly and continue to react for 6-8h, remove the solvent, and obtain multi-arm polyethylene glycol; The modified POSS comprises the following raw materials, by mass: 15-20 parts of octahydroxybutylated cage-shaped silsesquioxane, 10-15 parts of 3,3,3-trifluoropropionyl chloride; the multi-arm polyethylene glycol comprises the following raw materials, by mass: 25-30 parts of modified POSS, 20-25 parts of four-arm epoxy polyethylene glycol; The second binder is polytetrafluoroethylene.

2. The method for preparing a high-stability lithium battery pole piece according to claim 1, characterized in that: The first bonding layer solution includes the following raw materials: 0.01-1.5 wt% of oxidized conductive filler, 0.5-1.5 wt% of a first bonding agent, and the rest is deionized water; in the raw materials of the modified active material, the mass ratio of the active material to the first bonding agent is (99-99.5): (0.5-1).

3. The method for preparing a high-stability lithium battery pole piece according to claim 1, characterized in that: In the raw materials of the composite active material, the mass ratio of the modified active material, the second binder and the conductive filler is (95-96): (1.5-2): (2-3).

4. The method for preparing a high-stability lithium battery pole piece according to claim 1, characterized in that: The preparation of the oxidized conductive filler comprises the following steps: oxidizing the conductive filler with 10-20wt% hydrogen peroxide for 1-10h, filtering, washing and drying to obtain the oxidized conductive filler; the conductive filler comprises one or more of carbon nanotubes, carbon fibers, graphene and conductive carbon black.

5. A high-stability lithium battery pole piece prepared according to the method for preparing a high-stability lithium battery pole piece according to any one of claims 1 to 4.

6. The high-stability lithium battery pole piece according to claim 5 is used in the preparation of lithium batteries.

Citation Information

Patent Citations

  • Preparation method of battery active layer, battery pole piece and application

    CN113659104A

  • Binder composition for anode, anode, and secondary battery

    CN113728470A